STUDY ON THE ROLE OF VIRGIN PARK AS AN ACTIVE RTH FOR TLOGOSARI AND SURROUNDING SOCIETIES - Ummi Hanifah Marshush; Hilmi Hilmansyah (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2023)
This research was structured to find out the role of Virgin Park as green open space which has intrinsic (ecological) and extrinsic (social, cultural, economic and aesthetic) functions, as well as the level of its role according to visitors' perceptions. This research uses descriptive analysis and scoring. The results showed that the positive and negative index values ​​were 999 and 981. The positive index values ​​were counted higher than the negative indexes. This indicates that respondents gave a positive response to the role of Virgin Park as an open green space that is actively used by the community. Calculations regarding the interpretation of the score to produce a classification level of the role of Virgin Park as an active green open space obtained results of 70.6% which fall into the classification level of a strong role. Supporting factors are the function of Virgin Park as an active green open space, namely the role of air circulation, entertainment and recreation facilities, a source of income for street vendors, and comfort.